Krzemieniec jako centrum oświatowe w zachodniej części Ukrainy na przestrzeni dziejów (XVIII–XX wiek) - Szmyt, Andrzej; Шмит, Андрій (My University, 2016)
У дослідженні зроблено спробу наукового аналізу маловідомих фактів історично-педагогічного процесу в XVIII–ХХ ст. До найважливіших із них належать виявлення та висвітлення особливостей організації навчально-виховної діяльності ліцею в Крем’янці. У науковий обіг упроваджено невідомі й маловідомі документи та матеріали, які значно розширили уявлення про розвиток освітніх закладів України у XVIII–XX ст.The study attempted to scientific analysis of little-known facts of historical and pedagogical process in XVIII - twentieth century. The most important of them is the identification and coverage features of educational activities Lyceum in Kremenec. In the scientific revolution introduced the unknown and little known documents and materials that have greatly expanded understanding of the development of educational institutions in Ukraine XVIII-XX century. The fate of institutions directly linked to the socio-political situation in the province.
Кременец как центр образования в Заманюй Украине на протяжении столетий
Keywords: Кременець; освіта; Волинський ліцей; Тадеуш Чацький; Kremenets; education; Volyn Lyceum; Tadeusz Chatsky